An Investigation Into the Reasons of Discontinuance of Japanese Amongst First Year Tertiary Students Who Have Studied Japanese to Year 13 at Secondary School - Oshima, Ryoko (Auckland University of Technology, 2011)
This study has used grounded theory to investigate the reasons New Zealand students cease learning Japanese language at the transition stage from secondary to tertiary education despite their successful learning of Japanese to Yr 13 at secondary school. The literature suggests that as a foreign language, Japanese is one of the more time-consuming languages to master and in many countries high student attrition rates among Japanese language learners, particularly at an early stage of their learning, have been a serious concern. Therefore, it is important to identify the reasons for discontinuance in order to eliminate problems and encourage students to continue their language learning. However, in New Zealand, major studies on student attrition in language learning were within the secondary sector and there has been little research done among long term language learners at the transition stage. The data collection was conducted through semi-structured interviews with sixteen participants from Auckland who studied Japanese to Yr 13 at secondary school but did not study at tertiary level. The interviews were transcribed and analysed using a grounded theory process for coding, comparative analysis and theoretical sampling. Findings revealed that while some participants considered continuing Japanese at tertiary level, some other participants did not have any intention to continue Japanese. Findings also revealed that the major reasons for discontinuance for those who had some intention to continue Japanese were either: having a concern over academic manageability in taking Japanese along with their major studies; and/or having a difficulty in access to the Japanese course. Recommendations and suggestions are made in the light of facilitating Yr 13 students of Japanese to continue Japanese at tertiary level. Further research on post-Yr 13 students of Japanese in other regions, and post-Yr 13 students of other languages who discontinued their language learning at tertiary level are also recommended.
Keywords: Japanese; Transition stage; Post-Year 13 students; Foreign language learners; Learner attrition; Study choices